Hubungan Perhatian Orang Tua Terhadap Hasil Belajar Siswa Kelas IV Sekolah Dasar - Mai Sri Lena; Hana Shilfia Iraqi; Annisaul Mutmainnah; Santi Oktavia (Lembaga Pengembangan Kinerja Dosen, 2023)
In education, the attention of parents is one factor that is very important and influences the education of their children. However, many parents underestimate their children's education. There are still many students who do not get enough attention from their parents in their studies. This is one of the factors in children's academic achievement that is not optimal. To improve learning outcomes, students must be motivated both internally and externally. This study discusses the problem of how the relationship between parental attention and student learning outcomes in grade IV elementary school. This type of research is qualitative with a descriptive approach. The source of the research material is the parents of elementary school students and their academic results. Observations, questionnaires and interviews were used as methods in data collection. The results showed that 15 students with a percentage of 71.42% received parental attention in the very good category, 4 students with a percentage of 19.04% in the good category, and 2 students with a percentage of 9.52% in the category of little parental attention. The average student learning outcomes in the very good category were achieved by 13 students with a percentage of 61.90%, in the good category were 6 students with a percentage of 28.57%, the less and less good categories each received 1 student with a percentage of 4.76%. . Thus, parental attention has a relationship with student academic results.